Feijoada as a concept of cultural/religious mixture. Issue 1 (2nd January 2022) - Engler, Steven
ABSTRACT: In order to avoid problematic assumptions, this article proposes a Brazilian culinary term, ' feijoada, ' as an etic term for concepts of cultural mixture. This emphasizes not what mixed cultural/religious forms are but of how we interpret their meaning. Feijoada is a synonym for 'mixture' in Brazilian Portuguese and it has been used in Brazilian social theory. It highlights the weakness of defining mixtures in terms of referential relations to prior elements that came–to–be–mixed. It emphasizes the ideological use of narratives of origins, not allegedly objective truths about those origins; it addresses decolonial critiques of temporality; and it focuses on social, cultural and regional contexts. Feijoada serves as a relatively empty placeholder for cultural/religious phenomena placed on our table: these call first for contextualized interpretation, and only later – if the case warrants – for the use of more prescriptive concepts as labels or models.